Placenta Accreta Spectrum Among Multiple Gestation: A Retrospective Analysis Based on a Chinese Population - Guo, Zhirong; Han, Xueyan; Zheng, Weiran; Yang, Huixia; Ma, Jingmei (Frontiers in Endocrinology, 2022)
Background: It is controversial whether women with multiple gestation are at higher risk of placenta accreta spectrum (PAS). Large-scale and homogeneous research is needed. This study aimed to assess whether PAS occurs more frequently among women with multiple gestation than among singletons, as well as to compare the characteristics and outcomes of PAS in multiple and singleton gestation. Methods: Women who underwent cesarean section with live births at Peking University First Hospital from January 2015 to December 2020 were included. Demographic and clinical information was collected through chart review. Logistic regression models were used to analyze the associations between multiple gestation and PAS. The clinical characteristics and perioperative outcomes of PAS in multiple and singleton gestation were further compared. Results: Among the 14583 women included, 2.4% (352/14583) were diagnosed with PAS. PAS was slightly more prevalent among multiple gestations than among singletons (2.5% vs 2.4%, P=0.857). After adjusting for known risk factors and pregnancy complications, multiple gestation was associated with a higher risk of PAS (aOR=1.63, 95% CI 1.01-2.62). Among PAS patients, women who had multiple births had a significantly lower rate of previous cesarean deliveries (27.6% vs. 56.3%, P=0.003), placenta previa (17.2% vs. 56.3%, P<0.001) and invasive PAS (24.1% vs. 53.9, P=0.002) than singletons. There were no significant differences in perioperative outcomes between these two groups. Conclusion: Multiple gestation could be independently associated with an elevated risk of PAS. The clinical characteristics of PAS in the multiple and singleton gestation groups differed significantly in cesarean delivery history and placenta previa. The results of this study may inform guidelines on the screening, early detection and timely intervention of PAS patients among women with multiple births.